2020
DOI: 10.1021/acs.jmedchem.0c00053
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of Membrane-Active Flavone Amphiphiles: Semisynthetic Kaempferol-Derived Antimicrobials against Drug-Resistant Gram-Positive Bacteria

Abstract: Because of the rapid increase in bacterial resistance, there is an urgent need for developing new antimicrobial agents to combat multidrug-resistant pathogens. In this study, we designed and synthesized a series of kaempferol derivatives as antimicrobial agents biomimicking the structural properties and biological functions of host defense peptides. After fine-tuning of hydrophobic and cationic hydrophilic moieties linked to the flavone scaffold of kaempferol, we obtained a lead compound (52) that displayed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…It is also worth noting that, when phloretin (2 e), an open-chain flavonoid with four free phenolic hydroxyl groups, was employed as glycosyl acceptor for glycosylation with D-arabinose, L-xylose, D-xylose and β-D-lyxose, the corresponding glycosylation products were still isolated with excellent stereoselectivity and regioselectivity even though moderate yields (48%-59%) were observed (Table 2, 3 ae, 3 be, 3 ce, 3 de, 3 ee). reacted with D-glucose (1 f), which gave 4-O-β-D-glucopyranoside-3-hydroxy methyl benzoate (11) in 23% as the only product. [35] Silybin (12) is a much more complex glycosyl acceptor for glycosylation due to the presence of five hydroxy groups with three different types on its skeleton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that, when phloretin (2 e), an open-chain flavonoid with four free phenolic hydroxyl groups, was employed as glycosyl acceptor for glycosylation with D-arabinose, L-xylose, D-xylose and β-D-lyxose, the corresponding glycosylation products were still isolated with excellent stereoselectivity and regioselectivity even though moderate yields (48%-59%) were observed (Table 2, 3 ae, 3 be, 3 ce, 3 de, 3 ee). reacted with D-glucose (1 f), which gave 4-O-β-D-glucopyranoside-3-hydroxy methyl benzoate (11) in 23% as the only product. [35] Silybin (12) is a much more complex glycosyl acceptor for glycosylation due to the presence of five hydroxy groups with three different types on its skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…[2] A large number of new flavonoid glycosides are continually identified from natural products every year, the true number is thus far more than that. Flavonoid glycosides are of great benefit to human health and have shown an extensive range of pharmacological activities, including anti-inflammatory, [3,4] antioxidant, [5][6][7] anti-tumor, [8,9] antibacterial, [10][11][12] hypoglycemic [13][14][15] and neuroprotective activity. [16,17] Even though the wide distribution and biological activities only very few methodologies on the synthesis of flavonoid glycosides have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the compound showed in vivo efficacy in the murine keratitis model . In another example, Lin et al synthesized a series of Kaempferol flavone derivatives by linking them to different cationic and hydrophobic moieties and evaluated for their antibacterial potential . A SAR study identified that the lipid chain is important for insertion of the compound into the bacterial membrane.…”
Section: Short Synthetic Peptides and Their Mimetics As Promising Ant...mentioning
confidence: 99%
“…Moreover, the observed activity was greatly affected by spacer lengths and p K a of amine groups, whereas reduction in activity was observed for synthesized analogues either with too short ( n < 2) or too long ( n ≥ 8) spacer lengths and also with amine groups of low p K a . Their lead compound showed in vivo efficacy in a murine corneal infection model …”
Section: Short Synthetic Peptides and Their Mimetics As Promising Ant...mentioning
confidence: 99%
See 1 more Smart Citation